1996
DOI: 10.1002/(sici)1097-4660(199606)66:2<169::aid-jctb478>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Lipase from Candida rugosa on Synthetic Polymer Beads for Use in the Synthesis of Fatty Esters

Abstract: Lipase from Candida rugosa was immobilized on three different supports, i.e. Amberlite XAD7, poly(methylmethacrylate) (PMMA) and celite. With the conditions tested, maximum adsorption can be achieved after 30 min. The activities of the immobilized lipases were determined by the esterification reaction of oleic acid and butanol. The immobilized lipases were found to be very effective in the esterification reaction. The immobilized activities generally were high in apolar organic solvents with log P values from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
4
16
0
1
Order By: Relevance
“…The maximum binding of the enzyme to CaCO 3 (95%) was achieved after incubation for 40 min. This was consistent with prior descriptions for the immobilization of R. oryzae and C. rugosa lipases to CaCO 3 and AmberliteXAD7, respectively [11,26].…”
Section: Immobilization Of S Aureus Lipasesupporting
confidence: 92%
“…The maximum binding of the enzyme to CaCO 3 (95%) was achieved after incubation for 40 min. This was consistent with prior descriptions for the immobilization of R. oryzae and C. rugosa lipases to CaCO 3 and AmberliteXAD7, respectively [11,26].…”
Section: Immobilization Of S Aureus Lipasesupporting
confidence: 92%
“…However, these findings indicated that lipase remained immobilised on LDH even after washing with 20 mL of hexane, indicating that LDHs are suitable as supports for immobilisation of lipase. Similar results have been reported by Basri et al (1996) in studying the abilities of polymer beads to hold the enzyme after a few cycles of washing with organic solvent. This provides additional advantages for the LDHs.…”
Section: Immobilisation Of Lipasesupporting
confidence: 78%
“…On the other hand, the lower activities of protease in the polar solvents could be due to the fact that these solvents could strip the essential water layer around the enzyme, which is important for enzyme catalysis (Basri et al, 1996). As it has early been recognized that water is necessary to preserve the active conformation of the enzyme and determine the catalytic activity (Klibanov, 1989;Yamane et.…”
Section: Effect Of Organic Solvents On Stability Of Alkaline Proteasementioning
confidence: 84%